Primary leiomyosarcoma in the inferior vena cava- a case report - Kumar, Ravindra; Chaudhary, Suman; Mishra, Hemant Kumar; Goyal, Divesh (International Journal of Research in Medical Sciences, 2017)
Vascular leiomyosarcoma of IVC is a rare tumor. Only about 200 cases have been reported worldwide. There is a strong predilection for females and middle segment of IVC is most commonly affected. The diagnosis is often challenging as patients present with non-specific complaints such as dyspnoea, abdominal discomfort, or back pain. A 43-year-old male presented with history of vague abdominal distention, discomfort, and dyspnoea in our hospital. Ultrasound of abdomen detected a mass in retro peritoneum with mixed echogenicity inseparable from IVC. CT Imaging examination of abdomen revealed a large elongated, heterogenous mass extending from right atrium to the confluence of common iliac veins. in IVC reaching up to inferior border of right atrium. Then USG guided biopsy done and Leiomyosarcoma of IVC was diagnosed by immunohistochemistry. Due to extensive involvement of intrahepatic segment and right atrium complete resection of mass was not possible, so radiotherapy followed by chemotherapy was started. Patient started deteriorating due to intolerability with poor response to radiotherapy and chemotherapy so he was put on supportive treatment.